PENERAPAN KONSEP TRI HITA KARANA DALAM DESAIN TAMAN LINKUNGAN PADA BANJAR MANIK SAGA DESA PANJER DI DENPASAR - Ni Made Emmi Nutrisia Dewi (Jurnal Lentera Widya, 2022)
The environmental park is one of the essential public facilities because it functions as a green open space and a place for outreach. A public park at Panjer Village, Banjar Manik Saga, in the Denpasar City area, has been a design concern. Due to the existing conditions that are less organized and maintained. Therefore the Bali Business and Design Institute community service team went directly to redesigning the environmental park. This report describes the process of community service activities by redesigning the Banjar Manik Saga environmental park in Panjer Village from beginning to completion. This report aims to provide an overview of the results of an ecological garden design so that it is aesthetically pleasing, functional and in harmony with the environment. The Tri Hita Karana concept is a design implementation of a park used as a worship place (existing as a temple) to add green open areas with various plants. These facilities also can be used for local people to socialize as park benches. Onward, the design has intended to obtain the advantage of the surrounding community so that there is harmony between God, the environment and society.